Preface: SiliconPV 2024, the 14th International Conference on Crystalline Silicon Photovoltaics - Sébastien Dubois (SiliconPV Conference Proceedings)
The SiliconPV 2024 conference brought together nearly 300 scientists and engineers from 27 countries, with 142 abstracts approved by reviewers and presented through 61 oral talks and 71 posters, both onsite and online. 10 submissions were retracted. The conference served as a vibrant platform for exchanging knowledge, sharing ideas, and fostering collaboration among PV experts worldwide.